Professionals’ Verdict on Video Instructional Package for Junior Secondary School Students in Basic Technology - Olabo, Obielodan Omotayo; Ochayi, Onojah Amos; Muhammed, Jimoh Joseph; Adebayo, Alimi Emmanuel; Aderogba, Onojah Adenike (Indonesian Journal of Teaching in Science, 2021)
Advances in technology have brought instructional media to the forefront as the most radical tools of globalization and social development which have influenced the classroom teaching/ learning situation positively. Such technological breakthroughs are important landmarks in knowledge transfer. There are several acclaimed video packages which may not be perfectly suitable for instruction thus there is need to evaluate any package that should be used for learning. The main purpose of this research was to investigate experts' evaluation on the video instructional package for junior secondary school students in basic technology. This research was a research and development research method and the respondents comprised of 20 experts studying at the University of Ilorin, Ilorin, Nigeria. The findings established that Experts rated the video instructional package to be very effective and good for learning. It was however recommended that Computer literacy programme should be provided for both students and teachers for full integration of ICT resources in Science Education Programme.